PЕRIPHRАSЕS АS А STYLISTIС DЕVIСЕ IN LINGUISTIСS - Аllаyоrоvа , Shаhnоzа (Educational Research in Universal Sciences, 2023)
The language has rich resources to make the language more colourful and interesting to be heard. Stylistic devices play an important role to deal with the quality of the language. To be more specific, periphrases is considered to be the important stylistics device in linguistics